Influence of mix design parameters on asphalt concrete aging rate using I-FIT specimens. (10th March 2019) - Zhu, Zehui; Singhvi, Punit; Espinoza-Luque, Arturo Francisco; Ozer, Hasan; Al-Qadi, Imad L.
Highlights: The I-FIT is an effective approach to capture asphalt concrete aging. The increase of ABR, effective asphalt content, and VMA, or a decrease of low-temperature true grade induce a decrease of aging rate. 1D/95C can be a reasonable and practical alternative long-term aging protocol for I-FIT. Abstract: Aging is considered an important factor contributing to the deterioration of asphalt concrete (AC) pavements. As a result of aging, the resistance of AC pavements to various forms of cracking including fatigue, thermal, or block is reduced. Therefore, it is critical to understand the effect of aging on AC pavement cracking development and identify the effect of AC mix design parameters on the aging rate. A wide range of AC surface mixes was investigated in this study using the Illinois Flexibility Index Test (I-FIT) after the specimens were subjected to various lab-simulated aging conditions. The flexibility index (FI), an I-FIT outcome parameter, decreases consistently after long-term aging. This effect is primarily due to changes in the post-peak slope, which represents crack growth rate. The effect of mix design parameters on FI deduction rate (or aging rate) was analyzed using statistical methods. Single and multiple linear regression techniques were implemented to identify the significant of AC mix design parameters on the aging rate. The effect of voids in mineral aggregate (VMA), low-temperature true grade, asphalt binder replacement (ABR), mix type, and effective asphalt content was found to be significant. The increase of ABR, effective asphalt content, and VMA, and/or a decrease of low-temperature true grade induce a decrease in the aging rate of AC.